2006
DOI: 10.1002/app.24196
|View full text |Cite
|
Sign up to set email alerts
|

Degradation characteristics of poly(ϵ‐caprolactone)‐based copolymers and blends

Abstract: ABSTRACT:The hydrolytic degradation of various bioresorbable copolymers and blends derived from -caprolatcone, d,l-lactide and poly(ethylene glycol) (PEG) was investigated at 37°C in a pH 7.4 phosphate buffer. Poly(-caprolatcone) (PCL) followed a slow degradation profile due to its hydrophobicity and crystallinity. The hydrophilicity and degradability of the materials can be improved by copolymerization with PEG and/or poly-(d,l-lactide) (PLA). Homogenous degradation was shown in the cases of PCL, PCL/PEG copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 24 publications
(36 reference statements)
5
76
0
Order By: Relevance
“…Although, when the content of PLA was greater than 40%, the rate of degradation was observe to increase as compared to that of the homopolymer 95 . The degradation kinetics of PCL extremely depends upon the molecular weight of the polymer.…”
Section: Synthesis Of Pclmentioning
confidence: 82%
“…Although, when the content of PLA was greater than 40%, the rate of degradation was observe to increase as compared to that of the homopolymer 95 . The degradation kinetics of PCL extremely depends upon the molecular weight of the polymer.…”
Section: Synthesis Of Pclmentioning
confidence: 82%
“…In addition, poly(ethylene glycol) (PEG) chains may be used as hydrophilic polymer to form a shell around PU NPs. This strategy to construct PEG layers on NPs has been attracting much interest in medical, pharmaceutical and biological areas due to their unique properties as PEG chains attached to the surface or forming the corona of a nanoparticle lead to rapid chain motion in an aqueous medium [25] and establish prolonged systemic circulation [4], [24] and [26].…”
Section: Introductionmentioning
confidence: 99%
“…Parameters affecting the controlled degradation of blends, apart from the properties of the components, include the composition, preparation method, compatibility and miscibility of the components [3,4]. Several blend pairs of biodegradable homo-and co-polymers have been studied, including materials composed of poly(3-caprolactone) (PCL), polyanhydrides, poly(ethylene glycol) (PEG), and poly(D,L-lactic acid) (PDLLA) [1,2,4]. Morphological and thermodynamic analyses of polymer blends have shown that PCL are immiscible but compatible with PEG [2,5] and PDLLA [6], whereas PDLLA and PEG have been reported to be miscible [7].…”
Section: Introductionmentioning
confidence: 99%
“…Its simplicity makes it preferable, in some cases, to co-polymerisation, which is laborious and time consuming. In the field of tissue engineering, blending two polymers with different degradation profiles may serve to tune physical and mechanical properties [1], or to achieve a desirable rate of degradation [2]. Parameters affecting the controlled degradation of blends, apart from the properties of the components, include the composition, preparation method, compatibility and miscibility of the components [3,4].…”
Section: Introductionmentioning
confidence: 99%